CH and NO planar laser-induced fluorescence and rayleigh-scattering in turbulent flames using a multimode optical parametric oscillator - Miller, Joseph D.; Tröger, Johannes W.; Engel, Sascha; Seeger, Thomas; Leipertz, Alfred; Meyer, Terrence R. (Applied Optics, 2021)
An optical parametric oscillator (OPO) is developed and characterized for the simultaneous generation of ultraviolet (UV) and near-UV nanosecond laser pulses for the single-shot Rayleigh scattering and planar laser-induced-fluorescence (PLIF) imaging of methylidyne (CH) and nitric oxide (NO) in turbulent flames. The OPO is pumped by a multichannel, 8-pulse Nd:YAG laser cluster that produces up to 225 mJ/pulse at 355 nm with pulse spacing of 100 µs. The pulsed OPO has a conversion efficiency of 9.6% to the signal wavelength of ∼430 nm when pumped by the multimode laser. Second harmonic conversion of the signal, with 3.8% efficiency, is used for the electronic excitation of the A-X (1,0) band of NO at ∼215 nm, while the residual signal at 430 nm is used for direct excitation of the A-X (0,0) band of the CH radical and elastic Rayleigh scattering. The section of the OPO signal wavelength for simultaneous CH and NO PLIF imaging is performed with consideration of the pulse energy, interference from the reactant and product species, and the fluorescence signal intensity. The excitation wavelengths of 430.7 nm and 215.35 nm are studied in a laminar, premixed CH4−H2−NH3–air flame. Single-shot CH and NO PLIF and Rayleigh scatter imaging is demonstrated in a turbulent CH4−H2−NH3 diffusion flame using a high-speed intensified CMOS camera. Analysis of the complementary Rayleigh scattering and CH and NO PLIF enables identification and quantification of the high-temperature flame layers, the combustion product zones, and the fuel-jet core. Considerations for extension to simultaneous, 10-kHz-rate acquisition are discussed.
CRIS-Team Scopus Importer:2021-01-08

Characterization of gas phase temperatures in dependence of particle presence in the flame spray pyrolysis process - Peukert, Wolfgang; Gao, Yi; Kögler, Andreas; Kilian, Daniel; Seeger, Thomas; Leipertz, Alfred; Engel, Sascha (CLEO: Applications and Technology, CLEO_AT 2012, 2012)
We introduce a novel strategy to acquire gas phase temperatures by O2 pure rotational CARS during flame spray pyrolysis (FSP) for silica production. RCARS benefits from a polarization filtering technique that is essential in particle and droplet environments. Particle containing regions were located by correlating laser-induced breakdown (LIB) in a particle-laden and a particle-free flame at different heights. Measured temperatures in the particle regime show significantly lower flame temperatures for particle-laden flames since energy is dissipated rapidly by radiation heat transfer in the presence of particles. ©2011 Optical Society of Americ
Keywords: gas; phase; flame; spray; pyrolysis; polarization; laser

Classification of Different Zones in a Flame Spray Pyrolysis Process - Münsterjohann, Bettina; Engel, Sascha; Kilian, Daniel; Will, Stefan; Peukert, Wolfgang (International Workshop Nucleation and Early Stages of Particle Formation, 2014)

Effect of particle presence on gas phase temperature in the flame spray pyrolysis - Peukert, Wolfgang; Engel, Sascha; Gao, Yi; Kögler, Andreas; Kilian, Daniel; Seeger, Thomas; Leipertz, Alfred (Nanotechnology 2012: Advanced Materials, CNTs, Particles, Films and composites (Volume 1), 2012)
For the production of manufactured nanoparticles at a commercial scale flame processes are most frequently used. An important basis for understanding the complexity of this process is the characterization of the combustion process in dependence of the operation conditions. As minor changes of process parameters have huge impact on the product, invasive classic methods would fail. Hence, there is a demand for non-invasive advanced optical measurement tools acquiring data regarding the flame and the particle formation without changing the product by the applied measuring technique. In this work, gas phase temperatures, significantly influencing product particle sizes, were acquired by O -based pure rotational CARS during flame spray pyrolysis (FSP) and were compared for a particle-free and a particle-laden flame. Furthermore, the influence of different precursor concentrations on the distribution of the liquid regime was investigated by Mie scattering.
Keywords: Flame spray pyrolysis; Nanoparticles; Rotational CARS; Spray combustion; Temperature measurement

Gas mixing analysis by the simultaneous application of two-dimensional Raman measurements and particle image velocimetry - Bräuer, Andreas; Engel, Sascha; Hankel, Robert; Leipertz, Alfred (Optics Letters, 2009)

Gas phase temperature measurements in a flame spray pyrolysis process by O2 pure rotational CARS - Peukert, Wolfgang; Seeger, Thomas; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Leipertz, Alfred (Laser Applications to Chemical, Security and Environmental Analysis 2012, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used. To preserve the original behavior of the sensitive flame spray pyrolysis process in situ, the gas phase temperatures were measured with pure rotational CARS. An O pure rotational CARS setup was applied due to the lack of N. The CARS technique benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. The temperature results indicate the dissipation of energy by radiation in the presence of particles since the flame temperatures are decreasing with increasing particle concentrations. © 2012 OS
Keywords: flame; spray; pyrolysis; gas; phase; particle; nano; radiation

Gas phase temperature measurements in the liquid and particle regime of a flame spray pyrolysis process using O2-based pure rotational coherent anti-Stokes Raman scattering - Peukert, Wolfgang; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Seeger, Thomas; Leipertz, Alfred (Applied Optics, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used where mostly oxygen is fed to the flame if high combustion temperatures and thus small primary particle sizes are desired. To improve the understanding of these complex processes in situ, noninvasive optical measurement techniques were applied to characterize the extremely turbulent and unsteady combustion field at those positions where the particles are formed from precursor containing organic solvent droplets. This particle-forming regime was identified by laser-induced breakdown detection. The gas phase temperatures in the surrounding of droplets and particles were measured with O2 -based pure rotational coherent anti-Stokes Raman scattering (CARS). Pure rotational CARS measurements benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. Due to different signal disturbing processes only the minority of the collected signals could be used for temperature evaluation. The selection of these suitable signals is one of the major problems to be solved for a reliable evaluation process. Applying these filtering and signal selection steps temperature measurements have successfully been conducted. Time-resolved, single-pulse measurements exhibit temperatures between near-room and combustion temperatures due to the strongly fluctuating and flickering behavior of the particle-generating flame. The mean flame temperatures determined from the single-pulse data are decreasing with increasing particle concentrations. They indicate the dissipation of large amounts of energy from the surrounding gas phase in the presence of particles.
Keywords: oxyide; nanoparticle; optical; noninvasive; droplet; combustion; raman; scattering

Optical Analysis and Material Characterization of Nanoparticulate Oxides Synthesized via Flame Spray Pyrolysis - Münsterjohann, Bettina; Engel, Sascha; Stanzel, Melanie; Kilian, Daniel; Herre, Patrick; Peukert, Wolfgang; Will, Stefan (2014 MRS (Materials Research Society) Fall Meeting and Exhibit, 2014)

Potential of two-line atomic fluorescence for temperature imaging in turbulent indium-oxide-producing flames - Münsterjohann, Bettina; Huber, Franz; Klima, Tobias; Holfelder, Sandra; Engel, Sascha; Miller, Joseph D.; Meyer, Terrence R.; Will, Stefan (Journal of Nanoparticle Research, 2015)
The applicability of two-line atomic fluorescence (TLAF) for temperature imaging in an indium-based flame spray pyrolysis (FSP) process is demonstrated using a single tunable optical parametric oscillator (OPO) to generate the required excitation wavelengths consecutively. Single-shot images of the detected fluorescence signals demonstrate that the signal levels in the flame are suitable for evaluation of temperature and verify the capability and potential of the measurement technique directly during particle formation without additional indium seeding. Qualitative averaged two-dimensional temperature distributions in the FSP flame are presented, showing the influence of varying sheath gas flow rates on the resulting temperature distribution. With the addition of a second OPO and detection system, the two fluorescence signals acquired consecutively in this work could be obtained simultaneously and enable spatio-temporally resolved single-shot temperature measurements in flame synthesis processes of indium-containing nanoparticles.
Keywords: Flame spray pyrolysis; Indium(III)-oxide nanoparticles; Two-line atomic fluorescence; Temperature measurement

Raman Mixture Composition and Flow Velocity Imaging with High Repetition Rates - Bräuer, Andreas; Engel, Sascha; Dowy, Stefan; Luther, Sebastian; Goldlücke, Jürgen; Leipertz, Alfred (Optics Express, 2010)

Simultaneous laser-induced fluorescence and Raman imaging inside a hydrogen engine - Engel, Sascha; Koch, Peter; Bräuer, Andreas; Leipertz, Alfred (Applied Optics, 2009)

Spatially resolved flame zone classification of a flame spray nanoparticle synthesis process by combining different optical techniques - Kilian, Daniel; Engel, Sascha; Borsdorf, B.; Gao, Yi; Kögler, Andreas; Kobler, S.; Seeger, Thomas; Will, Stefan; Leipertz, Alfred; Peukert, Wolfgang (Journal of Aerosol Science, 2014)
Flame spray synthesis of silica nanoparticles is characterized by a set of complementary optical techniques. By means of laser-sheet based Mie scattering imaging, 2D-chemiluminescence imaging and coherent anti-Stokes Raman spectroscopy (CARS) local information on spatial droplet distribution, combustion zone, nucleation zone and temperature in the flame could be obtained. In addition, the outcomes from optical metrology are validated by thermophoretic sampling at different flame heights and the synthesized powders were analyzed by N2 gas sorption. By comparing these results the flame can be quantitatively classified into three distinct zones: (i) the droplet zone where precursor atomization and evaporation take place, (ii) the nucleation zone indicated by SiO*/Si* radicals as a preliminary species before SiO2 particle formation and (iii) the sintering zone characterized by the highest temperatures in flame. In addition the spatial spreading of the nucleation zone as a function of precursor concentration is investigated. Theoretical calculations and experimental results show an extended nucleation regime for the lowest precursor concentration compared to higher concentrations. Although this study is performed with hexamethyldisiloxane (HMDS) precursor to synthesize silica nanoparticles as a model system, dimensionless analysis shows that the results, concerning the spray formation, can be transferred to the synthesis of other materials as well.

Temperature and multi-species measurements by supercontinuum absorption spectroscopy for IC engine applications - Engelbrecht, Rainer; Will, Stefan; Werblinski, Thomas; Engel, Sascha; Zigan, Lars (Optics Express, 2013)
The first supercontinuum (SC) absorption spectroscopy measurements showing the feasibility of quantitative temperature evaluation are presented to the best of the authors' knowledge. Temperature and multi-species measurements were carried out at a detection rate of 2MHz in a high-temperature flow cell within a temperature range from 450K to 750K at 0.22MPa, representing conditions during the suction and compression stroke in an internal combustion (IC) engine. The broadband SC pulses were temporally dispersed into fast wavelength sweeps, covering the overtone absorption bands 2v1, 2v3, v 1 + v3 of H2O and 3v3 of CO 2 in the near-infrared region from 1330 nm to 1500 nm. The temperature information is inferred from the peak ratio of a temperature sensitive (1362.42 nm) and insensitive (1418.91 nm) absorption feature in the v1 + v3 overtone bands of water. The experimental results are in very good agreement with theoretical intensity ratios calculated from absorption spectra based on HiTran data. © 2013 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2013.tech.IE.LEH.temper_3

Temperatur- und Multi-Spezies-Messung in der Verbrennungstechnik mittels Supercontinuum-Absorptionsspektroskopie - Werblinski, Thomas; Engel, Sascha; Engelbrecht, Rainer; Zigan, Lars; Will, Stefan (Thermodynamik-Kolloquium 2013, 2013)

Time-Domain Based Absorption Spectroscopy: A Comparison of ns-and ps-Pumped Supercontinuum Sources for IC Engine Applications - Werblinski, Thomas; Engelbrecht, Rainer; Engel, Sascha; Will, Stefan; Zigan, Lars (European Combustion Meeting 2013, 2013)
lhft_intern.bib::werblinski13